Mediator analysis of passion for work in Indian millennials: Relationship between protean career attitude and proactive work behavior. Issue 1 (13th February 2017) - Gulyani, Gaatha; Bhatnagar, Jyotsna
Abstract : Purpose: The purpose of this paper is to examine the relationship between protean career attitude (PCA) and proactive work behaviors (PWB) and with the theoretical underpinning of self-determination theory to ascertain if passion for work acts as a mediator for PCA and PWB. Design/methodology/approach: A survey of 255 millennial employees working in diverse industries in India (such as information technology, banking and education) was conducted. Regression analysis was used to measure the direct effects of the hypothesized relationships. Sobel test and bootstrapping analysis were used to measure the indirect effects of the hypothesized relationship. Findings: PCA assists in fostering passion for work. Passion for work is positively related with PWB and fully mediates the relationship between PCA and PWB. Practical implications: Employers should provide flexibility in work design and autonomy in career decisions. Also, Human resource managers should provide career growth opportunities to retain millennial talent. Originality/value: This study bridges the knowledge gap between different domains of knowledge including PCA, passion for work and PWB. This study is one of the rare attempts to understand the relationship between PCA and PWB through the lens of passion for work. It also bridges the gap relating to its context. With an increasing number of millennials in workforce in India, an understanding of their career attitudes and outcome behaviors has become a significant concern. The results of the present study underpin career motivation theory, self-determination theory and generational cohort theory.